Animated Video Design of Motion Graphic-Based Passenger Guide Ships at Port of Bandar Deli - Beby Aprilia Kesuma (Cattleya Darmaya Fortuna, 2022)
In a port, a guide is an important part to build a good image and assessment so that it can be the main choice of the people, to make it easier to guide passengers and to the wider community, increasingly advanced technology is needed. The purpose of making a Motion Graphic-Based Animation Video for Passenger Ship Guides at the Port of Bandar Deli is to make the video guide an effective means of obtaining a complete interactive guide to prospective ship passengers at the port of Bandar Deli. Animated Videos This guide was designed using Adobe Illustrator and Adobe After Effects software. In this study, Motion Graphic animation will be used to make animated videos as a guide for prospective ship passengers